PENGEMBANGAN INDUSTRI KECIL DAN MENENGAH MELALUI PEMBUATAN APLIKASI MARKETPLACE “LAPAK CIANJUR” - Herlambang, Herlambang (Nindikayla Institute, 2023)
The economic growth of the Cianjur district is quite satisfactory even though previously it was down due to the Covid-19 pandemic which has occurred almost all over the world. Currently, the Cianjur regency government continues to encourage various commodity players to market intensively outside the region and even abroad. On this basis, an effective and more efficient marketing tool is needed, namely the marketplace application for business people in Cianjur Regency. This community service activity was carried out to help develop the lapakcianjur application to outreach to business people in Cianjur district